2021
DOI: 10.3390/insects12050413
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Regulatory Mechanism of FoxO on Wing Dimorphism in the Brown Planthopper, Nilaparvata lugens (Hemiptera: Delphacidae)

Abstract: The brown planthopper (BPH), Nilaparvata lugens, can develop into either short-winged (SW) or long-winged (LW) adults according to environmental conditions, and has long served as a model organism for exploring the mechanisms of wing polyphenism in insects. The transcription factor NlFoxO acts as a master regulator that directs the development of either SW or LW morphs, but the underlying molecular mechanism is largely unknown. Here, we microinjected SW-destined morphs with double stranded-RNA (dsRNA) targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…, 2020; Xu et al. , 2021). An analogous phenotype was found in D. melanogaster , in which loss of FoxO suppressed the reduction in cell number, and overexpression of FoxO caused reduced cell number (Jünger et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2020; Xu et al. , 2021). An analogous phenotype was found in D. melanogaster , in which loss of FoxO suppressed the reduction in cell number, and overexpression of FoxO caused reduced cell number (Jünger et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on how different cell types respond–either by producing resistance chemicals or activating other molecular processes –to BPH feeding are lacking. Therefore, we selected 48 h post-infestation time for this study based on previous results that show significant changes in gene expression occurring between 24–48 hours of BPH infestation of rice leaves ( Liu Y. et al., 2021 ; Xu et al., 2021a ; Xue et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA replication and cell cycle have rarely been focused on as regulatory mechanisms of density-dependent polyphenism [ 33 ]. A recent study [ 42 ] showed that the regulation of DNA replication and the cell cycle is involved in the density-dependent wing polyphenism of the planthopper Nilaparvata lugenes . Together with this study, our results emphasize the importance of DNA replication and the cell cycle as the regulatory mechanisms of density-dependent polyphenism.…”
Section: Discussionmentioning
confidence: 99%